Haemagglutination induced by Bordetella pertussis filamentous haemagglutinin adhesin (FHA) is inhibited by antibodies produced against FHA(430-873) fragment expressed in Lactobacillus casei - Colombi, Debora; Oliveira, Maria L. S.; Campos, Ivana B.; Monedero, Vicente; Perez-Martinez, Gaspar; Ho, Paulo L. (Springer, 2006)
Filamentous haemagglutinin adhesin (FHA) is an important virulence factor from Bordetella pertussis related to the adhesion and spread of the bacteria through the respiratory tract. Three distinct domains have been characterized in mature FHA, and among them, the FHA(442-863) fragment was suggested to be responsible for the heparin-binding activity. In this study, we cloned the gene encoding the HEP fragment (FHA(430-873)) in a Lactobacillus casei-inducible expression vector based on the lactose operon. The recombinant bacteria, transformed with the resulting construct (L. casei-HEP), were able to express the heterologous protein depending on the sugar added to the culture. Subcutaneous inoculation of L. casei-HEP in Balb/C mice, using the cholera toxin B subunit as adjuvant, induced systemic anti-HEP antibodies that were able to inhibit in vitro erythrocyte haemagglutination induced by FHA. This is the first example of a B. pertussis antigen produced in lactic acid bacteria and opens new perspectives for alternative vaccine strategies against whooping cough.